Association Between Sleep Quality and Self-Efficacy Trajectories Among Pregnant Women: A Parallel Process Latent Growth Curve Model - Mei X; Li Y; Wu X; Liang M; Chen Q; Kang L; Ye Z (Nature and Science of Sleep)
Xiaoxiao Mei,1 Yan Li,1 Xiaona Wu,2 Minyu Liang,3 Qianwen Chen,3 Limei Kang,4 Zengjie Ye5 1School of Nursing, Hong Kong Polytechnic University, Hong Kong, People’s Republic of China; 2School of Management, Shanwei Institute of Technology, Shanwei, People’s Republic of China; 3School of Nursing, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 4Department of Obstetrics, Jiangmen Central Hospital, Jiangmen, People’s Republic of China; 5School of Nursing, Guangzhou Medical University, Guangzhou, People’s Republic of ChinaCorrespondence: Limei Kang, Email kanglimei1@163.com Zengjie Ye, Email zengjieye@qq.comBackground: Sleep quality is essential for pregnant women and affects their self-efficacy. However, the longitudinal dynamics between these constructs, particularly regarding personality traits, are not well understood. This study aimed to examine the relationship between sleep quality and self-efficacy trajectories among pregnant women, as well as the role of maternal personality traits.Methods: A prospective cohort design was employed, utilizing consecutive sampling. Pregnant women were assessed at four-time points from early pregnancy to 42 days postpartum. Self-efficacy, sleep quality, and personality traits were evaluated using validated scales. Latent profile analysis and parallel process latent growth curve modeling were employed for data analysis.Results: Poorer initial sleep quality negatively predicted initial self-efficacy (β=− 0.459, P< 0.05) but positively predicted self-efficacy growth rate (β=0.383, P< 0.05). Worsening sleep quality over time was associated with lower self-efficacy growth (β=− 0.405, P< 0.05). These relationships were significant only for women with mild emotional instability, not those with moderate emotional stability.Conclusion: Sleep quality and self-efficacy are closely linked among pregnant women, with maternal emotional stability moderating this association. Further research is warranted to elucidate the underlying mechanisms.Keywords: pregnant women, self efficacy, sleep quality